Ukrainian adaptation of the nomenclature of the International Consensus on Antinuclear Antibody Patterns - Ye.V. Tarasov; M.M. Kurtova; I.H. Koltsova; A.Yu. Shevchuk; O.A. Gruzevskiy (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Diagnosis of autoimmune diseases remains a complex multi-stage process that includes various methods of laboratory testing. The gold standard for serological diagnosis of autoimmune connective tissue disorders is the indirect immunofluorescence assay (IFA) on HEp-2 cells. The result of the test is a description of the morphological pattern observed in the assay, which correlates with the corresponding autoantibodies and allows to direct further diagnostics. The most recent and most comprehensive attempt to describe HEp-2 IFA patterns was made by the International Consensus on Antinuclear Antibody (ANA) Patterns (ICAP).